[Chaos Theory and Its Application in Nursing Science] - Vicenzi, Angela (1995)
Keywords: dept.nur; faculty_collection; sabbatical_report

Contemporary Legal Issues Affecting Professional in Human Service Fields. - Killion, Susan (1992)
Keywords: dept.nur; faculty_collection

A Nursing Home and Its Organizational Climate: An Ethnography - Farmer, Bonnie Cashin (Auburn House, 1996)
Keywords: Case studies; Case studies; Corporate culture; Meadows of Madison (Nursing home); Nursing homes; Sociological aspects; dept.nur; faculty_collection

The Pediatric Survival Guide - Rebeschi, Lisa M.; Brown, Mary L. (Skidmore-Roth Pub., 1996)
Keywords: dept.nur; faculty_collection

The sundown syndrome: Will the specialized training of nurse's aides help elders with sundown syndrome? - Wallace, M. (Geriatric Nursing, 1994)
3 citations (Crossref) [2023-10-31]
Keywords: Aged; Humans; Nurses' Aides; Social Behavior Disorders; Time Factors; aged; article; dept.nur; human; nursing; nursing assistant; sociopathy; time

Nursing Diagnosis in Home Care: Audit Tool Development - Zink, M.R. (Journal of Community Health Nursing, 1994)
Little research has been done to document the value of using nursing diagnosis in home care and the impact that increased acuity levels have had in diagnostic selection. Nursing diagnosis documentation in home care was examined to see whether it had a relation to select client and visit pattern variables. This retrospective chart audit, which piloted a newly developed instrument called the Home Care Audit Tool, utilized a sample of 199 closed records of a large midwestem Visiting Nurse Association. The mean age of the client population was 76 years, with 64% female. There were 269 initial nursing diagnoses cited in the sample records, averaging 1.75 diagnoses per case. The number of recorded visits increased when select nursing diagnoses were cited together in a single case. © 1994, Taylor & Francis Group, LLC. All rights reserved.
5 citations (Crossref) [2023-10-31]
Keywords: Aged; Community Health Nursing; Female; Home Care Services; Human; Male; Models; Nursing; Nursing Audit; Nursing Diagnosis; Nursing Records; Pilot Projects; Reproducibility of Results; Retrospective Studies; Severity of Illness Index; article; community care; dept.nur; home care; medical assessment; nursing; nursing education

Nursing ethics committees —where are they? - Zink, M.R.; Titus, L. (Nursing Management, 1994)
When establishing Nursing Ethics Committees (NECs), statewide nursing organizations play an important role in developing and disseminating resources. The Connecticut Nurses Association Ethics and Human Rights Committee surveyed 85 healthcare facilities to identify active NECs. Representatives facilitated other committees by providing guidelines and assistance to those agencies developing NECs — the ultimate goal. © 1994 by Springhouse Corporation.
2 citations (Crossref) [2023-10-31]
Keywords: Bioethics and Professional Ethics; Clinical Approach/Source; Connecticut; Empirical Approach; Ethics Committees; Ethics Committees; Clinical; Ethics; Nursing; Human; Patient Advocacy; Questionnaires; Survey; United States; article; dept.nur; human; human rights; medical ethics; organization and management; professional standard; questionnaire; survey

Dual assignment: An alternative clinical teaching strategy - Fugate, T.; Rebeschi, L.M. (Nurse Educator, 1992)
Meeting students’ learning needs in acute care settings is challenging. The authors discuss dual assignment in the pediatric setting with beginning nursing students. © 1992 Lippincott-Raven Publishers.
1 citations (Crossref) [2023-10-31]
Keywords: Clinical Competence; Education; Nursing; Baccalaureate; Human; Pediatric Nursing; article; competence; dept.nur; education; human; methodology; nursing; nursing education; standard

Dual assignments: An effective clinical teaching strategy - Gotschall, L.A.; Thompson, C. (Nurse Educator, 1990)
0 citations (Crossref) [2023-10-31]
Keywords: dept.nur

Caring for a young child in a body cast: Impact on the care giver - Newman, D.M.L.; Fawcett, J. (Orthopaedic Nursing, 1995)
Data from an open-ended questionnaire and the comments section of a structured questionnaire were combined and ana-lyzed to determine the challenges faced and alterations in usual daily activities required by mothers caring for a young child at home in a body cast. The sample consisted of 35 mothers who identified themselves as the primary care givers of a child in a body cast. The challenges of caring for a child in a body cast required major adjustments in almost every aspect of the mothers' lives, including household activities, social and community activities, child care activities, personal care activities, occupational activities, and educational activities. © 1995 National Association of Orthopaedic Nurses.
17 citations (Crossref) [2023-10-31]
Keywords: Adolescent; Adult; Caregivers; Casts; Surgical; Child; Preschool; Cost of Illness; Female; Hip Dislocation; Congenital; Home Nursing; Human; Infant; Infant; Newborn; Male; Mothers; Questionnaires; Support; Non-U.S. Gov't; adolescent; adult; article; caregiver; congenital hip dislocation; cost of illness; dept.nur; education; female; home care; human; infant; male; mother; newborn; nursing; plaster cast; preschool child; psychological aspect; questionnaire

Creutzfeldt-Jakob disease. Assessment and management update. - Wallace, M. (Journal of gerontological nursing, 1999)
3 citations (Crossref) [2023-10-31]
Keywords: *Creutzfeldt-Jakob Syndrome/nu [Nursing]; Aged; Creutzfeldt Jakob disease; Creutzfeldt-Jakob Syndrome; Creutzfeldt-Jakob Syndrome/cl [Classification]; Creutzfeldt-Jakob Syndrome/pp [Physiopathology]; Creutzfeldt-Jakob Syndrome/px [Psychology]; Humans; MLCS; MLOWN; Male; Middle Aged; Nursing Assessment; Nursing Assessment/mt [Methods]; Patient Care Planning; Prognosis; Risk Factors; aged; case report; classification; dept.nur; human; male; methodology; middle aged; nursing; nursing assessment; pathophysiology; patient care planning; prognosis; psychological aspect; review; risk factor

Meeting the learning needs of diverse students in BSN programs. - Thompson, C (Nurse educator, 1998)
4 citations (Crossref) [2023-10-31] Place: United States Thompson, C. Department of Nursing, Southern Connecticut State University, New Haven, USA.
Keywords: *Cultural Diversity; *Education; Nursing; Baccalaureate/mt [Methods]; *Students; Nursing; Cultural Diversity; Education; Nursing; Baccalaureate; Humans; Learning; MLCS; MLOWN; Students; Nursing; article; cultural anthropology; dept.nur; human; learning; methodology; nursing education; nursing student

Chaos in nursing: make it work for you. - Vicenzi, A E; White, K R; Begun, J W (The American journal of nursing, 1997)
Place: United States Vicenzi, A E. Department of Nursing, Southern Connecticut State University, New Haven, USA.
Keywords: *Health Facility Environment; *Nurses/px [Psychology]; *Nursing; Adaptation; Psychological; Humans; Interprofessional Relations; Organizational Innovation; dept.nur; ❓ Multiple DOI

Critical thinking skills of baccalaureate nursing students at program entry and exit - Thompson, C; Rebeschi, LM (Nursing and Health Care Perspectives, 1999)
Most nurse educators would agree that critical thinking is an essential competency for the professional nurse in today's ever-changing health care environment. In fact, critical thinking has been identified as an integral component of professional nursing practice and has been incorporated in accreditation guidelines (1-3). As a result of this imperative, professional programs of nursing must explicate a clear definition of critical thinking, identify specific learning outcomes reflective of critical thinking abilities, and select appropriate ways to measure the achievement of these outcomes in graduating students. Although much has been written about the need for critical thinking skills, the concept and measurement of critical thinking within the context of nursing education has not yet been clearly defined (4-6). As a result, nursing programs are developing their own conceptual definitions of critical thinking and using a variety of methods to measure outcomes (5). The authors caution that to ensure validity of findings, the instruments used must reflect the individual program's definition of the concept. In most cases, outcomes have been assessed using a cross-sectional design that compares students at different levels or types of programs or are measured as an end-of-program outcome. While such designs can provide educators with knowledge of students' critical thinking abilities at a particular point in the educational process, longitudinal data are needed to assess the effects of the educational program.
tex.unique-id: ISI:000085103900006
Keywords: *Clinical Competence/st [Standards]; *Education; Nursing; Baccalaureate/og [Organization & Administration]; *Educational Measurement/mt [Methods]; *Nursing Process; *Program Evaluation/mt [Methods]; *Students; Nursing/px [Psychology]; *Thinking; Accreditation; Clinical Competence; Education; Nursing; Baccalaureate; Educational Measurement; Humans; Nursing Education Research; Nursing Process; Outcome Assessment (Health Care); Outcome Assessment; Health Care; Program Evaluation; Research Design; Students; Nursing; Thinking; accreditation; article; clinical competence; dept.nur; education; health care quality; human; methodology; nursing education; nursing process; nursing student; organization and management; outcome assessment; psychological aspect; standard; thinking; ⛔ No DOI found

Outcomes assessment: implications for nursing education. - Thompson, Cesarina; Bartels, Jean E (Journal of Professional Nursing, 1999)
In response to public criticisms about the outcomes of higher education, colleges and universities have implemented comprehensive assessment programs. In nursing education, outcomes assessment has become a criteria for accreditation. Yet, currently no guidelines exist describing “best practices” in nursing education outcomes assessment. Experts in educational assessment provide helpful guidelines for nurse educators as they establish comprehensive assessment plans. The authors provide a review of the literature in the field of assessment and offer strategies for developing successful assessment programs in nursing education.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/151-849-929-326-658 tex.type: [object Object]
Keywords: *Benchmarking/og [Organization & Administration]; *Education; Nursing/st [Standards]; *Guidelines as Topic; *Outcome Assessment; Health Care/og [Organization & Administration]; *Program Evaluation/mt [Methods]; Accreditation; Accreditation/og [Organization & Administration]; Benchmarking; Curriculum; Education; Nursing; Guidelines; Humans; Nursing education; Outcome Assessment (Health Care); Outcomes assessment; Program Evaluation; Program evaluation; accreditation; curriculum; dept.nur; health care quality; human; methodology; nursing education; organization and management; outcome assessment; practice guideline; quality control; review; standard

Focus on community: directions for nursing knowledge development - Kulbok, Pamela A; Gates, Marie F; Vicenzi, Angela E; Schultz, Phyllis R (Journal of Advanced Nursing, 1999)
Nurses are challenged to advance the theoretical foundations of community practice. This paper offers ideas on what-has been done and what needs to be done to meet this challenge. Within a community health nursing perspective, the paper defines community, proposes an integrated knowledge development framework that focuses on community, analyses contemporary theoretical and philosophical foundations of community in nursing, considers three worldviews in which nursing can be framed, and examines parameters for knowledge development for the future.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-438-110-171-942 tex.type: [object Object]
Keywords: Community; Community Health Nursing; Community health nursing; Humans; Knowledge; Knowledge development; Nursing; Nursing Theory; Nursing theory; Philosophy; Post-modernism; Professional Practice; World-view; article; community health nursing; dept.nur; human; knowledge; nursing; nursing theory; professional practice

The application of nonlinear dynamics in nursing research - Hamilton, Patti; Pollock, Jane Englebright; Mitchell, null De Ann F.; Vicenzi, Angela E.; West, Bruce J. (Nonlinear Dynamics, Psychology, and Life Sciences, 1997)
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00201 tex.type: [object Object]
Keywords: dept.nur

Differences in Classroom Teaching Preferences between Traditional and Adult BSN Students - Thompson, C.; Sheckley, B.G. (Journal of Nursing Education, 1997)
The primary purposes of this study were to identify the best teaching practices for adult baccalaureate (BSN) nursing students and to examine if adult students' teaching preferences differed from those of traditional BSN students. The sample consisted of 206 adult and traditional students in four BSN programs. The adult nursing student sample was further subdivided into two groups: adults with no prior nursing education (adult non-nurses) and adults with prior nursing education (RN'S). Using a two-part, self-administered questionnaire, respondents were asked to rate the frequency with which 41 teaching strategies were used in their best and in their worst classroom learning experiences in nursing. In most cases, adult non-nurses' teaching preferences did not vary significantly from the preferences of traditional students. However, adults with no prior nursing education did show a preference for knowledgeable and organized instructors. In contrast RNs' preferred classroom situations were where time on task was emphasized, cooperative learning was encouraged, and expectations for learning were high. Results indicate that classroom teaching preferences vary as a function of prior experience with the subject matter and are not attributable to age itself. Findings suggest that prior experience with course content is a more important consideration in planning programs than generalized adult experience.
26 citations (Crossref) [2023-10-31]
Keywords: *Choice Behavior; *Education; Nursing; Associate; *Education; Nursing; Baccalaureate; *Education; Professional; Retraining; *Students; Nursing/px [Psychology]; *Teaching/st [Standards]; Adolescent; Adult; Choice Behavior; Education; Nursing; Associate; Education; Nursing; Baccalaureate; Education; Professional; Retraining; Factor Analysis; Statistical; Humans; Middle Aged; Nursing Education Research; Questionnaires; Students; Nursing; Surveys and Questionnaires; Teaching; adolescent; adult; article; comparative study; continuing education; decision making; dept.nur; factorial analysis; human; middle aged; nursing education; nursing student; psychological aspect; questionnaire; standard; teaching

Chaos theory and some nursing considerations - Vicenzi, Angela E (Nursing Science Quarterly, 1994)
The alleged synthesis of nursing and public health has not produced the expected community-as-client emphasis. Public health is characterized as disease-focused, with masculine domination, using a causal model. The explanatory model of chaos challenges nurses to reexamine nursing's theoretical base by questioning assumptions associated with linear thinking. The selected chaotic concepts of aperiodicity, attractors, sensitive dependence on initial conditions, phase space, and fractals are discussed here. Each concept's connection to physics and mathematics is cited and considerations for nursing science are outlined. Conclusions include redefining health, nursing, and community in chaotic terms and renaming nursing practice, which has this aperiodic and holistic paradigm, as ecologic health nursing.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/119-144-108-349-30X tex.type: [object Object]
Keywords: Chaos Theory; Community Health Nursing; Fractals; Human; Models; Nursing; Nonlinear Dynamics; Rogers; Thinking; article; dept.nur; fractal analysis; human; model; nonlinear system; nurse; thinking

Chaos Theory and Nursing Revisited: Commentary and Response - Zbilut, J.P.; Staffileno, B.; Vicenzi, A.E. (Nursing Science Quarterly, 1994)
3 citations (Crossref) [2023-10-31]
Keywords: Human; Nonlinear Dynamics; Nursing Theory; dept.nur; human; nonlinear system; note; nursing; ⛔ No DOI found

Social support systems in elder homebound clients - Zink, Margo R (Home Health Care Management & Practice, 1994)
An individual's social support system comprises multiple networks. A lack in one system may cause an increased need for support in another. Social support has been found to be of vital impor tance to the health of the older adult client and caregiver. It has been found to have a significant influence on health outcomes, acting as a buffer and altering recovery patterns. This article de scribes the concept of social support and relates how the home health care nurse can assess this dimension and use the findings to better plan patient care in the home setting. Key words: social support, home care, older adult. © 1994, Sage Publications. All rights reserved.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-578-813-060-298 tex.type: [object Object]
Keywords: dept.nur

Case commentary: Bass v. Barksdale: implications for public health and home care nurses - Killion, Susan Westrick (Public Health Nursing, 1993)
A recent malpractice case involved public health nurses. Given the legal issues based on this case, recommendations can be made to help ensure legal accountability, improve practice, and minimize liability risk. Areas of concern include doctor's orders and communication relating to telephone orders, the nurse's accountability to the client, documentation and patient teaching, the physician's duty to supervise the nurse, and corporate negligence. The court's analysis of the facts in finding areas of liability can guide nurses in avoiding malpractice litigation.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/039-112-513-700-590 tex.type: [object Object]
Keywords: Community Health Nursing; Ethambutol; Female; Human; Liability; Legal; Malpractice; Nursing Records; Patient Education; Public Health Nursing; Tennessee; United States; Vision Disorders; article; dept.nur; ethambutol; female; human; iatrogenic disease; legal aspect; legal liability; malpractice; medical record; nurse; patient education; public health service; visual disorder

AIDS education on the college campus: Roy's adaptation model directs inquiry - Vicenzi, Angela E; Thiel, Robert (Public Health Nursing, 1992)
We assessed the beliefs of 49 college students regarding the acquired immunodeficiency syndrome (AIDS), condom use, and sexual behaviors related to AIDS prevention. Roy's modes of self-concept, interdependence, and role function were used as a framework to find psychosocial determinants that influence safer sex practices. Interdependence was measured by a sexual regard scale. Beliefs regarding both AIDS beliefs and condom were very positive. Students were selectively using safer sex practices; most reported avoiding high-risk partners, but only 39% were using condoms. No significant associations were found among the four independent measures of AIDS beliefs, condom beliefs, self-esteem, and sexual regard or with the dependent measure, AIDS safer sex practices. A two-hour safer sex educational module did change several beliefs but did not increase safer sex practices. Most participating students stated they had a good understanding of how AIDS was spread, they knew how to use condoms correctly, and they discussed AIDS with friends and parents.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/075-551-621-168-730 tex.type: [object Object]
Keywords: dept.nur

Collaborative project to examine social support in elder homebound diabetics - Zink, Margo R; Gadomski, Mary; Oconnell, Patricia Buckley; Nizziherzog, Marie (Home Health Care Management & Practice, 1992)
Social support has a significant effect on the response to illness and treatment. The au thors present some of the findings and practical applications originating from a collaborative study, including a clinical indicator tool for the diabetic patient. This information gives the home health care professional an expanded knowledgebase to use in developing individualized care plans for the elder home care diabetic. © 1992, Sage Publications. All rights reserved.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/090-204-733-259-335 tex.type: [object Object]
Keywords: dept.nur

Nurse Manners' Guide to Politically Correct Behavior - Vicenzi, Angela E (Journal of Nursing Scholarship, 1991)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/063-975-520-464-024 tex.type: [object Object]
Keywords: Human; Nurses; Social Behavior; Wit and Humor; article; dept.nur; human; humor; nurse; psychological aspect; social behavior